[Nowy Port, ul. Oliwska 66] [Aut. odb. Karol Nowaliński]. - Nowaliński, Karol (1935- ). (Karol Nowaliński, 1986)
Przedstawia dom nr 66 przy ul. Oliwskiej w Nowym Porcie, po prawej widoczny sklep mięsny Benjamina Roesler'a, ok. 1915 r.